Analysis Of The Use Of Project Based Learning On Students' Conceptual Understanding Ability In Statistics Material In Grade - Novlia Naibaho; Lena R. Pangaribuan; Sanggam P. Gultom (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to analyze the effect of the Project-Based Learning model on students' conceptual understanding of statistics in eleventh-grade students at SMA Negeri 2 Lubuk Pakam in the 2025/2026 academic year. The study used a descriptive qualitative approach, with 32 eleventh-grade students as subjects. Data were collected through a conceptual understanding test and a questionnaire assessing student responses to the Project-Based Learning model. The test instruments were tested for validity, reliability, difficulty level, and discriminatory power before use. The results showed that 12.5% of students had high conceptual understanding, 71.9% had moderate, and 15.6% had low. Project-based learning provided a more active learning experience, enhancing students' motivation, analytical skills, and collaboration in understanding statistics. However, students still faced challenges in interpreting statistical data and using statistical operations appropriately. Teachers play a crucial role in providing intensive guidance to address these challenges. Thus, the Project-Based Learning model effectively improves students' conceptual understanding, as well as their critical and creative thinking skills in statistics learning.